Pengaruh Inovasi Digital Terhadap Transformasi Industri Fesyen dalam Ekonomi Kreatif: Studi Systematic Literature Review - Muh. Jusman; Ghina Attikah; Rinda Syaharani; May Syaroh (TEKNOBIS : Jurnal Teknologi, Bisnis dan Pendidikan, 2026)
Digital transformation has fundamentally reshaped the fashion industry, shifting the paradigm from a linear economy to a sustainable circular model. This article aims to analyze the role of digital innovations such as 3D simulation, augmented reality, and blockchain in driving this transition, as well as to examine the influence of organizational dynamic capabilities and data fairness dimensions on the adoption of digital fashion as an end product. Using the Systematic Literature Review (SLR) method on publications from 2021–2025 sourced from Taylor & Francis and DOAJ databases, this study concludes that digital fashion not only revolutionizes value creation based on “idea capital” but also requires the integration of adaptive organizational capabilities and ethical data governance practices. The synergy between technological innovation, organizational agility, and fair data principles is key to realizing a resilient, inclusive, and sustainable fashion ecosystem within the global creative economy.